Is the promotion of physical activity in vulnerable older people feasible and effective in general practice? - Dinan, Susie (Oxford University Press, 2006)
There is convincing evidence about the benefits of exercise training in community dwelling frailer older people, but little evidence that this intervention can be delivered in general practice. In this prospective cohort study in 14 general practices in north London we assessed the feasibility and effectiveness of a tailored exercise referral programme for frail elderly patients delivered within a variety of inner city primary care settings. One hundred and twenty-six women and 32 men aged 75 years and older, deemed borderline frail by their GPs, took part in a two-phase progressive exercise programme (Stage 1 — primary care setting; Stage II — leisure/community centre setting) using the Timed Up And Go (TUG) test as the primary outcome measure. Baseline TUG measures confirmed that the participants were borderline frail and that GP selection was accurate. Of those referred by their GP or practice nurse 89% took up the exercise programme; 73% completed Stage I and 63% made the transition to the community Stage II programme. TUG improved in Stage I with a mean difference of 3.5 seconds (P<0.001). An individually tailored progressive exercise programme following GP referral, delivered in weekly group sessions by specialist exercise instructors within general practices, was effective in achieving participation in exercise sessions and in improving TUG values in a significant number of frailer older citizens.